Utilização de resíduos da extração do amido da mandioca seco na alimentação de ruminantes - Fernandes, Tatiane (2014)
In the production of ruminants there is the possibility of using agroindustrial residue in feeding, due to the capacity these animals present of ruminal fermentation. Many residues can be used, among which we highlight the cassava starch extracting residue, which presents considerable nutritional quality for ruminant feeding, as well as high availability in regions close to the cassava processing industries. With the objective of evaluating the use of dry cassava starch extraction residue (dCSER) in ruminant feeding, we performed studies to evaluate the in vitro digestibility and in situ degradability of dCSER and maize, as well as determine the appropriate level of dCSER to replace the maize in cattle diet, evaluating the fermentative parameters. For this purpose we used four castrated oxen, with rumen cannula, individually fed with diets containing increasing levels (0, 33, 66 and 100%) of dCSER replacing maize, to evaluate the dry matter and nutrient intake, in vivo digestibility, evaluation of pH and ammonia nitrogen of rumen fluid at different times (0, 2, 4, 6 and 8) after feeding. The dCSER presented differences regarding DM, OM and NDF in vitro digestibility when compared to maize, but did not present changes regarding NDT and in situ degradability. As for the in vivo evaluations, DM and nutrients intake was influenced, in a decreasing manner, by the treatments, resulting in changes in DM, OM and NDT digestibility, causing reduction in the NH3-N concentration, not influencing the pH. The cassava starch extraction residue presented nutritional traits similar to those of the maize. Its use in ruminant feeding improves fermentation characteristics in up to 100% of replacement, requiring further studies so that it does not interfere with the intake. In a second phase, we performed a study to evaluate the inclusion of dCSER in the diet of lactating cows, with the objective of measuring the influence of the residue replacement on intake, performance, and metabolic condition of these animals, as well as the economic feasibility of its use. For this study, we used four lactating cows, fed diets containing increasing levels (0, 33, 66 and 100%) of dCSER as replacement of maize. We observed reduction in dry matter, organic matter, crude protein, ether extract, total carbohydrates and acid detergent fiber intake, without interfering in neutral detergent fiber intake. Such variations did not affect the apparent digestibility of the nutrients. We also observed reduction in milk production, without any changes in the efficiency of milk production and in milk components, but with changes in the daily production of lactose, solids and minerals. The metabolic parameters were affected by the treatments, but remained within appropriate levels for these animals. The use of dCSER in ruminant feeding is an alternative to maize as an energy source, in total or partial replacement. However, more studies must be conducted in order to provide strategies, and its use should be linked to the product‟s profitability, since the acquisition of this residue, already dry, is not feasible